Analisis Aspek Teknis dan Operasional pada Kedai Kopi Skala Kecil: Studi Kelayakan Bisnis Boss L Coffee Corner - Dini Vientiany; Dela Arum Lestari; Aprilia Eka Putri; Husna Salsabila Siregar; Muhammad Fiqi Hafiz (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The coffee shop business, as part of the MSME sector, is growing rapidly, in line with the growing coffee drinking culture in society, especially among the younger generation. This situation has encouraged the emergence of various coffee shop businesses with diverse concepts, including Café Boss L Coffee Corner, located in Deli Tua, Deli Serdang Regency. This study aims to analyze the feasibility of Café Boss L Coffee Corner from a technical and operational perspective as part of a business feasibility study. The research method used was a qualitative approach, with data collection techniques through interviews, observation, and documentation. The data obtained were analyzed to assess the readiness of facilities and infrastructure, facility layout, equipment, operating hours, and service process efficiency. The results of the study indicate that Café Boss L Coffee Corner has a strategic location, adequate facilities, and an effective and efficient operational system appropriate for the scale of an MSME business. Furthermore, the feasibility study indicates that this business meets the feasibility criteria from a technical, operational, market, and economic perspective. Therefore, Café Boss L Coffee Corner is deemed feasible to operate and develop as a business with potential for sustainability and good future profit opportunities.